Pernikahan Menurut Himpunan Penghayat Kepercayaan Terhadap Tuhan Yang Maha Esa Temanggung Jawa Tengah - Mariati, Isa (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2014)
This article discusses the implementation process of marriage contract according to the Almighty God Seeker Association in Temanggung regency, Central Java. The marriage contract conducted by the Almighty God Seeker Association is in line with the guideline of marriage horoscope book Betaljemur Adammakna as a reference for the wedding procession, consisting of a groom and a bride, and a marriage contract without a guardian. While, the terms of marriage are determination, noble intention, mutual agreement, and blessing of the family. The marriage contract is performed in the office of the Almighty God Seeker Association and is done with the current belief that they trust. The marriage guidelines are forth in the regulation on the Almighty God Seeker Association. They are about keys of religious harmony, conditions of NGOs establishment in accordance with the Government Regulation no. 37 of 2007 chapter x article 81-83 of the requirements and procedures for marriage registration for the trust seekers. Marriage for the Almighty God Seeker Association in term of Islamic law is invalid because it is not in accordance with the Islamic Law Compilation chapter IV, article 14 of the pillars of marriage that include prospective husband, groom and bride, guardian of marriage, two witnesses, and contract. [Artikel ini membahas tentang proses pelaksanaan akad nikah menurut Himpunan Penghayat Kepercayaan Terhadap Tuhan Yang Maha Esa di Kabupaten Temanggung Jawa Tengah. Pernikahan yang dilakukan oleh Himpunan Penghayat Kepercayaan Terhadap Tuhan Yang Maha Esa ini merupakan pernikahan yang memakai pedoman kitab primbon Betaljemur Adammakna sebagai acuan untuk melakukan prosesi pernikahan, dengan rukun pernikahan yang terdiri dari calon suami, calon istri dan Ä«jÄb qabÅ«l tanpa wali.Â  Sedangkan Syarat-syarat pernikahannya adalah tekad, niat suci, saling sepakat dan restu dari keluarga. Pernikahan dilakukan di kantor Himpunan Penghayat Kepercayaan Kepada Tuhan Yang Maha Esa dan dilakukan sesuai aliran kepercayaan yang mereka percayai. Panduan pernikahan tertuang dalam Peraturan tentang Penghayat Aliran Kepercayaan Terhadap Tuhan Yang Maha Esa, Kunci Kerukunan Umat Beragama, Syarat-Syarat Pendirian Ormas/LSM, yang sesuai dengan PP 37 Tahun 2007 dalam Bab X pasal 81-83 tentang persyaratan dan tata cara pencatatan perkawinan bagi penghayat kepercayaan. Pernikahan bagi Himpunan Penghayat Kepercayaan Terhadap Tuhan Yang Maha Esa ditinjau dari hukum Islam tidak sah, karena tidak sesuai dengan Kompilasi Hukum Islam bab IV pasal 14 tentang rukun perkawinan yang meliputi calon suami, calon istri, wali nikah, dua orang saksi, ijab dan qabul.]